The Design of Web Based Information System for 'Bintang Multi Sparepart Store' - Surbakti, F P S; Selly, (International Journal of Scientific Research and Management (IJSRM), 2023)
The advancements in information technology have provided many conveniences in the process of recording and reporting. Bintang Multi Sparepart Store is a business that sells automotive supplies. Its business process is divided into product sales, product stock fulfilment, and sales report creation. Based on the ongoing business process, sales recordings are done manually with a book, which increases the risk of errors due to spills and dirt on the book, tears, and human error. This results in inaccurate sales report calculations. Information about product availability also often has errors due to inaccurate information. In view of the problems that are occurring, this study designed an integrated information system that can collect, store, and process data to produce accurate information by applying the System Development Life Cycle (SDLC) principles, programming language PHP and MySQL for database storage, and through unit testing, integration testing, system testing, and acceptance testing. The designed information system is operating well, and the entire process in the information system meets the user's needs in terms of functionality and usability. The implementation of the proposed information system allows the owner to monitor all business processes, including transaction data and product data. The proposed information system is also capable of storing, summarizing, and presenting the entire sales transaction data in real time. In addition, the designed information system can process calculation on transaction data to be presented in the form of an accurate sales report, and there is a manual to make the information system operation process easier.